A nullor approach to the design of analog circuits for a desirable performance. (August 2018) - Radhakrishnan, Rohith Krishnan; Sukumarapillai, Krishnakumar; Hashemian, Reza
Abstract: A method for the performance design of analog amplifier circuits based on nullors is discussed. It covers the design of AC parameters of the amplifier viz. input and output resistance, gain and bandwidth. Fixator-norator pair, which is a combination of nullor and sources, is the key element in this method. The complete performance design is considered as a two step process. Fixator-norator pair along with the linear equivalent model of the target circuit together does the first step, which is the design for input and output resistance and gain. The second step performs the design for bandwidth, i.e., mainly the cut-off frequencies. This is based on Bode plot analysis, which requires a reference circuit having the same frequency response as that of the desired one. The reference circuit is required only for simulation and it can be removed after the final design is met. Four examples are worked out for better understanding of the method. Graphical abstract: